Pemanfaatan Opac sebagai Media Temu Kembali Informasi di Perpustakaan Universitas Muhammadiyah Makassar - Tasbih; Nur Farah Syahidah (Literatify: Trends in Library Developments, 2024)
This study aims to determine the optimization of OPAC, the factors that influence users to use OPAC, and the obstacles faced by users in utilizing OPAC as a medium for retrieving information at the Muhammadiyah University Library Makassar. The method used in this research is descriptive qualitative research. Data were collected through direct observation and in-depth interviews with librarians and users. Data analysis involves collecting, reducing, assessing, and interpreting data critically to reach conclusions. The results showed that: First, the factors that influence library users in utilizing OPAC, namely increasing the productivity and effectiveness of collection searches, as well as facilitating the activity of retrieving library materials needed by users without the need to search one by one on the collection shelves. Second, the obstacles faced in utilizing OPAC, namely frequent network disruptions when users use OPAC, the lack of ability of users to search through OPAC, and the mismatch of information between the display in OPAC and the existence on the collection shelves